Improving the quality of service of real-time database systems through a semantics-based scheduling strategy. (24th November 2020) - Achour, Fehima; Bouazizi, Emna; Jaziri, Wassim
A real-time database management system (RTDBMS) aims to manage applications with a large number of data being accessed by update and user transactions having to meet some time constraints. We are interested in improving the quality of service (QoS) in RTDBMSs by optimising the execution of transactions to improve meeting their deadlines. A new scheduling strategy is developed and evaluated into a QoS management architecture called feedback control scheduling (FCS) proposed for RTDBMSs. The proposed strategy is based on the new advanced earliest deadline first based on transactions aggregation and data semantic links (AEDF-TAL-DSL) protocol we developed. It introduces new parameters relating to the aggregation links (defined according to the type of operations composing the transactions and the data they access) existing between transactions as well as the semantic links appearing between the users' queries. We also show the contributions provided by our approach through simulation results.